LITERATUR REVIEW : PENERAPAN BATUK EFEKTIF DAN FISIOTERAPI DADA UNTUK MENGATASI KETIDAKEFEKTIFAN BERSIHAN JALAN NAFAS PADA KLIEN YANG MENGALAMI TUBERCULOSIS (TBC) - Wahyu Widodo, Siska Diyah Pusporatri (AKPER Pemkab Purworejo, 2020)
Tuberculosis is a disease caused by mycobacterium tuberculosis that get into respiratory tract and the lungs so that there was rash in alveoli or inflammation, the alveolar walls then will shrink. The prevalence of tuberculosis based on doctor diagnosis by provience 2013-2018 indonesia occupies 0,4% of the population. Purpose : The Purpose of writing literature review is to conduct research on clients who have tuberculosis with ineffective airway clearance. Method : The method research used by analyzing articles and searching through google scholar by using the keywords “chest physiotherapy and effective cough”, “chest physiotherapy and effective cough”+”tuberculosis”, “management of effective cough and chest physiotherapy” + “tuberculosis”, “effect of effective cough and chest physiotherapy” + “tuberculosis”. Results : The result from 5 journals found that there was a change in breathing rhythm, are able t secrete, shorthnes of breath decreases after effective coughing and chest physiotherapy. Conclusions : The conclutions application of effective cough and chest physiotherapy in tuberculosis patients who experience ineffective airway clearance can reduce shortness breath and spuntum and it is recommended that client can do effective chough and chest physiotherapy independently